Wie man’s nimmt. Zum Zusammenhang von Rassentheorien und Humor in den Schriften von Fritz von Herzmanovksy-Orlando: [How you look at it. The relations between grotesque humour and racial theories in the writings of Fritz von Herzmanovsky-Orlando] (Studia austriaca, 2017)
This article discusses the relationship between grotesque humor and racial theories in the works of Fritz von Herzmanovsky-Orlando. The humor of his literary works comprises deviant characters and slips of the tongue, exposing a penchant for physiological and philological deviations. In his esoteric writings, ariosophic legends and etymological acumen serve to reconstruct inhabitants and languages of a fallen age. The author’s humor is thus based on political beliefs of the 1920’s, rendering him, his people and language greater than they could actually be.